France : Financial Sector Assessment Program-Technical Notes-Stress Testing Methodology and Results; Integration into Global Financial Markets; and Public Intervention in Financial Markets-Obstacles to Monetary Transmission. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
These Technical Notes on France explain integration of global financial markets. The stress tests for the France Financial Sector Assessment Program (FSAP) were designed to yield as comprehensive and detailed a picture as possible within the constraints of the approach. Retail activity by foreign banks in France is small, but significant. The financial landscape in France remains characterized by a large number of idiosyncrasies that affect monetary transmission. Macroeconometric models point to a smaller reaction to monetary policy in France than in other large euro-area economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet